2022
DOI: 10.1099/ijsem.0.005379
|View full text |Cite
|
Sign up to set email alerts
|

Genome-based, phenotypic and chemotaxonomic classification of Faecalibacterium strains: proposal of three novel species Faecalibacterium duncaniae sp. nov., Faecalibacterium hattorii sp. nov. and Faecalibacterium gallinarum sp. nov.

Abstract: Faecalibacterium prausnitzii is one of the most important butyrate-producing bacteria in the human gut. Previous studies have suggested the presence of several phylogenetic groups, with differences at the species level, in the species, and a taxonomic re-evaluation is thus essential for further understanding of ecology of the important human symbiont. Here we examine the phenotypic, physiological, chemotaxonomic and phylogenomic characteristics of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
1
43
1
2
Order By: Relevance
“…We also observed strain specific growth response when inositol was given as a carbon source. Recently, a branch of F. prausnitzii , including A2-165 strain has been reannotated into a new species Faecalibacterium duncaniae [52], further highlighting the diverse metabolic potential of F. prausnitzii . Interestingly, it was reported that neither F. duncaniae nor F. prausnitzii grew on inositol, which contrasts with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed strain specific growth response when inositol was given as a carbon source. Recently, a branch of F. prausnitzii , including A2-165 strain has been reannotated into a new species Faecalibacterium duncaniae [52], further highlighting the diverse metabolic potential of F. prausnitzii . Interestingly, it was reported that neither F. duncaniae nor F. prausnitzii grew on inositol, which contrasts with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…When the microbiota communities of the challenged and unchallenged birds were investigated in more detail, it was observed that Faecalibacterium and Megamonas genera were reduced in the challenged groups compared to the non-challenged group. Faecalibacterium prausnitzii is the most well-characterized species of the Faecalibacterium genus, and other species have recently been identified and reported, including F. moorei ( 19 ), F. butyricigenerans, F. hominis, F. longum ( 20 ), F. duncaniae, F. gallinarum , and F. hattorii ( 21 ). Most Faecalibacterium bacteria are butyric acid producers, therefore they can exhibit anti-inflammatory effects and are potential probiotics for the treatment of gut inflammation ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In view of these facts, increasing research has focused on this particular gut bacterium, which has been proposed as a potential next-generation probiotic ( 14 ). This has accelerated research into this bacterial group, and expanding comparative genomic investigation has led to a proposed separation of former F. prausnitzii species into different Faecalibacterium species, including F. longum , F. butyricigenerans , F. prausnitzii , F. duncaniae; F. hattorii , and F. gallinarum , together with a number of still unassigned Faecalibacterium species ( 15 17 ). Thus, a word of caution should be given as most literature up to the past year referred exclusively to F. prausnitzii species, while several of the strains have been recently reclassified into novel separate species.…”
Section: Introductionmentioning
confidence: 99%